Clinical efficacy of therapeutic footwear with a rigid rocker sole in the prevention of recurrence in patients with diabetes mellitus and diabetic polineuropathy: A randomized clinical trial - López-Moral, Mateo (PLoS One, 2019)
BACKGROUND: Therapeutic footwear becomes the first treatment line in the prevention of diabetic foot ulcer and future complications of diabetes. Previous studies and the International Working Group on the Diabetic Foot have described therapeutic footwear as a protective factor to reduce the risk of re-ulceration. In this study, we aimed to analyze the efficacy of a rigid rocker sole to reduce the recurrence rate of plantar ulcers in patients with diabetic foot. METHODS: Between June 2016 and December 2017, we conducted a randomized controlled trial in a specialized diabetic foot unit. PARTICIPANTS AND INTERVENTION: Fifty-one patients with diabetic neuropathy who had a recently healed plantar ulcer were randomized consecutively into the following two groups: therapeutic footwear with semi-rigid sole (control) or therapeutic footwear with a rigid rocker sole (experimental). All patients included in the study were followed up for 6 months (one visit each 30 ± 2 days) or until the development of a recurrence event. MAIN OUTCOME AND MEASURE: Primary outcome measure was recurrence of ulcers in the plantar aspect of the foot. FINDINGS: A total of 51 patients were randomized to the control and experimental groups. The median follow-up time was 26 [IQR—4.4—26.1] weeks for both groups. On an intention-to-treat basis, 16 (64%) and 6 (23%) patients in the control and experimental groups had ulcer recurrence, respectively. Among the group with >60% adherence to therapeutic footwear, multivariate analysis showed that the rigid rocker sole improved ulcer recurrence-free survival time in diabetes patients with polyneuropathy and DFU history (P = 0.019; 95% confidence interval, 0.086–0.807; hazard ratio, 0.263). CONCLUSIONS: We recommend the use of therapeutic footwear with a rigid rocker sole in patients with diabetes with polyneuropathy and history of diabetic foot ulcer to reduce the risk of plantar ulcer recurrence. TRIAL REGISTRATION: ClinicalTrials.gov NCT02995863.